A qualitative evidence synthesis of users' experience of mobile health applications in the self-management of type 2 diabetes. (March 2022) - O'Neill, Margaret; Houghton, Catherine; Crilly, Geraldine; Dowling, Maura
Aim: The aim of this qualitative evidence synthesis was to identify and synthesise qualitative research relating to experiences of using mobile health (mHealth) applications to aid self-management of Type 2 Diabetes. Methods: Using a systematic search strategy, 11 databases were searched (Medline, CINAHL, PsychInfo, PubMed, Web of Science, Embase, Cochrane Library, Scopus, ProQuest A&1, ProQuest UK & Ireland, Mednar). "Best fit" framework synthesis was used guided by the Health Information Technology Acceptance Model (HITAM). Assessment of methodological limitations was conducted using Critical Appraisal Skills Programme (CASP) and confidence in the review findings were guided by GRADE-CERQual. Results: Fourteen eligible studies were included in the synthesis (7 qualitative and 5 mixed methods). Key themes identified under the health, information and technology zones of the HITAM revealed the benefits of mHealth apps, barriers to their use, their perceived usefulness and ease of use. Discussion: Most people used the apps for feedback on their self-management and found them helpful in their communication with health care providers. Some embraced the technology and found it easy to use while others found mHealth apps to be counterintuitive.